2020
DOI: 10.48550/arxiv.2007.10364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for dominant phonon-electron scattering in Weyl semimetal WP$_{2}$

Gavin B. Osterhoudt,
Vincent M. Plisson,
Yaxian Wang
et al.

Abstract: Topological semimetals have revealed a wide array of novel transport phenomena, including electron hydrodynamics, quantum field theoretic anomalies, and extreme magnetoresistances and mobilities. However, the scattering mechanisms central to these behaviors remain largely unexplored. Here we reveal signatures of significant phonon-electron scattering in the type-II Weyl semimetal WP 2 via temperature dependent Raman spectroscopy. Over a large temperature range, we find that the decay rates of the lowest energy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Until recently, this work on CDW transport was focused on quasi-1D systems, where the single-particle gap could be viewed as originating from nesting of a single-band Fermi surface. However, the discovery of Weyl semimetals [28][29][30][31][32][33][34][35] and their anomalous transport properties [36][37][38][39][40][41][42][43][44] has sparked interest in the phenomena that emerges when the CDW order opens a gap between Weyl fermions of opposite chirality [38,[45][46][47][48][49][50][51]. Theoretically, it has been shown that for a magnetic Weyl-CDW, the CDW phase couples to the electromagnetic field as a dynamical electromagnetic theta angle.…”
mentioning
confidence: 99%
“…Until recently, this work on CDW transport was focused on quasi-1D systems, where the single-particle gap could be viewed as originating from nesting of a single-band Fermi surface. However, the discovery of Weyl semimetals [28][29][30][31][32][33][34][35] and their anomalous transport properties [36][37][38][39][40][41][42][43][44] has sparked interest in the phenomena that emerges when the CDW order opens a gap between Weyl fermions of opposite chirality [38,[45][46][47][48][49][50][51]. Theoretically, it has been shown that for a magnetic Weyl-CDW, the CDW phase couples to the electromagnetic field as a dynamical electromagnetic theta angle.…”
mentioning
confidence: 99%
“…Some recent Raman spectroscopic studies further signify the importance of electronphonon scattering among microscopic scattering processes on the transport properties of Weyl semimetals. 223,224 Since, electronelectron interaction is not a dominating factor for most of the topological semimetals, understanding the electron-phonon interaction is essential to explore hydrodynamic effects in this broad class of materials.…”
Section: Electron Hydrodynamicsmentioning
confidence: 99%
“…Until recently, this work on CDW transport was focused on quasi-1D systems, where the single-particle gap could be viewed as originating from nesting of a single-band Fermi surface. However, the discovery of Weyl semimetals [28][29][30][31][32][33][34][35][36] and their anomalous transport properties [37][38][39][40][41][42][43][44][45] has sparked interest in the phenomena that emerges when the CDW order opens a gap between Weyl fermions of opposite chirality [39,[46][47][48][49][50][51][52]. Theoretically, it has been shown that for a magnetic Weyl-CDW, the CDW phase couples to the electromagnetic field as a dynamical electromagnetic theta angle.…”
mentioning
confidence: 99%